Projective drawing as a method of studying a family relationship - Lebedeva, Liudmila D. (Social Welfare: Interdisciplinary Approach, 2011)
The present article deals with the author’s original technique of studying social-communicative welfare and disability in family relationships by means of projective drawing. “The drawing of the family in flower images” belongs to the type of expressive methods based on psychological mechanism of projection, it has a metaphoric sense, actualizes imagination and the author’s image of emotional and sensual interfamily relations.The author’s technique reveals new possibilities in the study of individuality of personality. The results of empirical research prove the effectiveness of “associative family image” in flower images in diagnostics and art-therapy of family situation.This scientific research was financed by RGNF within the project integration № 11-06-00480а